2011
DOI: 10.1088/0266-5611/27/12/125006
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the parameters of cancellous bone by inversion of effective velocities, and transmission and reflection coefficients

Abstract: Estimating the parameters of an elastic or poroelastic medium from reflected or transmitted acoustic data is an important but difficult problem. Use of the Nelder-Mead simplex method to minimize an objective function measuring the discrepancy between some observable and its value calculated from a model for a trial set of parameters has been tried by several authors. In this paper, the difficulty with this direct approach, which is the existence of numerous local minima of the objective function, is documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The publication of Buchanan et al [30], although applying to a different canonical scattering body (their's is a poroelastic panel), is of interest here because:…”
Section: Numerical Results In a Case Analogous To That Of Buchanan Etmentioning
confidence: 99%
See 2 more Smart Citations
“…The publication of Buchanan et al [30], although applying to a different canonical scattering body (their's is a poroelastic panel), is of interest here because:…”
Section: Numerical Results In a Case Analogous To That Of Buchanan Etmentioning
confidence: 99%
“…[35] Moreover, the method can fail to converge or converge to non-stationary solutions in certain classes of problems. [36,37] Nevertheless, the Simplex algorithm has been frequently employed, particularly in parameter estimation problems, [30,[38][39][40][41] and even in problems involving noisy data. [42,43] Although Byatt et al [37] have reported on a supposedly-improved version (less function calls for a given value of the minimum of the cost function), we preferred to employ the off-the-shelf standard Simplex algorithm embodied in the MATLAB function f minsearch.…”
Section: The Simplex Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…• it is of interest to applications in the field of underwater acoustics, material wave characterization, or civil engineering for natural or artificial media [1][2][3][4][5][6][7][8],…”
Section: Model and Configuration Under Studymentioning
confidence: 99%
“…Obtaining structural images of a porous material, and estimating its physical properties, is a topic of considerable interest in many branches of activities in geophysics, underwater acoustics, civil engineering, and biomechanics [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%